Computer sciences student competency system for Information System Engineering (CS226) in UiTM Shah Alam - Rusdi, Muhammad Afiq (2013)
This project is to identify the technical skills expected by the industry on Information System Engineering (CS226) students. The user requirement for the system is identified for the development of the system. The system is about a development of a system which would match the competency of students with industry demands. Students will be evaluated by the supervisor during the class and industry supervisor during their practical for every semester. From the evaluation, the students will know their technical skills and understanding of the subjects they learn in every semester. The student will then be recommended their suitable jobs and technical skills required for the job. On top of that, the system will suggest university on which technical skills and course to provide in the syllabus of a program. The system will also provide industries access to find students that met their requirement to fit a role in their organizations. The project will be focusing on Information System Engineering (CS226) students as to match what the university supplied to CS226 students to match the industry needs. The development of the system will be based on rapid construction as the system is built from one stage to another until the completion of the system. There are 25 CS226 students have respond to survey which were given out during the process of the project. The survey resulted on the user requirement for the system. The system is build based on the response of the survey. In conclusion, the system is built to help university to meet the industry demands on graduated students in term of their technical skills. Meeting industry demands would reduce unemployment of graduate and produce the students that meet the objective of the university. In the future, the system shall be upgraded with more functionality and flexibility to complete a system that is required by the university. The system can be upgraded from time to time.